Comportamento das variáveis hidrológicas do balanço hídrico do solo em lisímetros de drenagem - Feltrin, Rafael Matias (2009)
The purpose of this study is the monitoring of the behaviour of variables involved in determining the hydrological water balance by means of lysimeters installed in a small basin in the central depression of Rio Grande do Sul. The controlled variables were the precipitation, the runoff, the infiltration and storage of water in the soil. This work also presents the procedures for installation and repair of one volumetric lysimeters, besides the physical characterization of the area studied. The evaluation of water balance through of lysimeters measures considered different time scales and the daily evapotranspiration were obtained for intervals of 5 and 10 days. Due to structural problems with the lysimeters the evaluation of variables runoff, infiltration and evapotranspiration was undermined during the period of repair of the lysimeters (June 2008 to December 2008), and these variables only was available after this period (January to April 2009). The variables precipitation and water storage in soil were evaluated during all the period studied (June 2008 to April 2009). The monitoring of the storage of water in the soil within the lysimeters was performed by means of tensiometers vaccum-type installed at depths of 10, 30 and 70 centimeter and then also analyzed by use of equipment TDR installed at 30 centimeter of depth, outside the lysimeters. The results showed that in wet periods the soil moisture is higher in the depth of 10 centimeter, whereas in dry periods there is a higher concentration of moisture at depth of 70 centimeter. The lowest values of moisture were obtained for depth of 30 centimeter both in wet and in dry period. The storage of water in the soil measured by tensiometers and TDR to the depth of 30 centimeter follows the same trend of variation, even with the tensiometers located inside the lysimeters and TDR outside it. However, the storage measured by the tensiometers was higher and presented more changes in relation to storage measured with TDR's help. The water balance in the daily scale developed from measures lysimeters through of the equipment referred in this study, does not show good results, especially in periods in which heavy rain occurs, overestimating or underestimating the evapotranspiration. Already for periods of 5 and 10 days, there are better results when compared with the daily scale.